2022
DOI: 10.1111/jnu.12804
|View full text |Cite
|
Sign up to set email alerts
|

Impact of advance care planning and end‐of‐life conversations on patients with cancer: An integrative review of literature

Abstract: Cancer is the leading cause of death worldwide, accounting for nearly 10 million deaths in 2020 (World Health Organization [WHO], 2021). It is the first or second leading cause of death before the age of 70 years in 112 of 183 countries and ranks third or fourth in further 23 countries (Sung et al., 2021). Global cancer Observatory, GLOBOCAN is a project of International Agency for Research on Cancer (IARC). According to GLOBOCAN, 2020 a total of 19.4 million new cancer cases were reported worldwide (excluding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…Penderita kanker yang dapat bertahan hidup lebih dari 5 tahun disebut sebagai survivor kanker. Dengan kondisi menderita sakit yang lama, penderita kanker memerlukan dukungan dari tenaga kesehatan yang terdapat dalam perawatan paliatif (Goswami, 2023b). Perawatan paliatif meningkatkan kualitas hidup pasien dan keluarga pasien yang menghadapi tantangan karena sakit yang mengancam jiwa, baik secara fisik, psikologis, social atau spiritual.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Penderita kanker yang dapat bertahan hidup lebih dari 5 tahun disebut sebagai survivor kanker. Dengan kondisi menderita sakit yang lama, penderita kanker memerlukan dukungan dari tenaga kesehatan yang terdapat dalam perawatan paliatif (Goswami, 2023b). Perawatan paliatif meningkatkan kualitas hidup pasien dan keluarga pasien yang menghadapi tantangan karena sakit yang mengancam jiwa, baik secara fisik, psikologis, social atau spiritual.…”
Section: Pembahasanunclassified
“…Pada kondisi stadium lanjut dimana pengobatan kanker sudah tidak dapat diberikan dan tujuan pengobatan bukan lagi untuk mengobati, perawatan paliatif menjadi solusi pilihan perawatan pasien yang dapat menyesuaikan dengan kebutuhannya sehingga kualitas hidup pasien kanker dapat meningkat, dan di saat waktunya sudah tiba, pasien dapat meninggal dengan bermartabat (PEDOMAN NASIONAL, 2015). Identifikasi pasien yang mungkin mendapat manfaat dari perawatan paliatif melalui alat identifikasi yang divalidasi, manajemen gejala multidimensi, dan diskusi tepat waktu tentang perencanaan awal merupakan elemen dari pendekatan perawatan paliatif untuk pasien dan keluarganya (Goswami, 2023b). Koordinasi antara pemangku kepentingan yang memberikan perawatan dan dukungan kepada pasien ini sangat penting untuk memastikan perawatan berkualitas tinggi dan memenuhi semua kebutuhan mereka (Vinant et al, 2017b).…”
Section: Pembahasanunclassified
“…Thirty-eight studies [15–52] and three reviews were identified [6 ▪ ,8 ▪▪ ,13 ▪▪ ]. Studies were heterogeneous in terms of cancer care contexts, population size and characteristics, research designs, and assessment methods (Table 1).…”
Section: Literature Search and Samplementioning
confidence: 99%
“…People with cancer face the need for complex, difficult decisions related to their treatment and end-of-life care to be made toward the ends of their lives, when their individual integrities are threatened and they are at greater risk of decision-making capacity impairment [1]. To support patient autonomy and ensure that care is aligned with patients’ goals, wishes, and values, oncology guidelines recommend advance care planning (ACP) [2–5], which involves voluntary ongoing discussion among patients, their relatives, and healthcare professionals (HCPs) about prognoses to understand, review, and plan for future end-of-life care decisions [6 ▪ ]. Despite the positive effects of ACP uptake, demonstrated by recent reviews [6 ▪ ,7,8 ▪▪ ,9], ACP remains under-implemented in routine cancer care [10,11 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation